Father, I don't want this marriage. 3 - Hong, Heesu; Yuri (Graphic novelist) (Inklore, 2025)
"Desperate to appear unavailable for marriage to the tyrannical Crown Prince Maximilian-the villain of her previous life-Juvelian has proposed a contract relationship with her father's rebellious protégé. At first glance, he's the perfect choice, but a veil of misunderstandings hides a dark truth that could challenge Juvelian's attempts to change her future. Meanwhile, political schemes and old grudges are moving in the shadows of the imperial court, and Juvelian's father, Duke Floyen, stands at the heart of them. As the crown prince seeks to solidify his power, the emperor tightens his hold over the duke"--